Ecowas, Democratic Governance and The Coup In Burkina Faso Fisher - Olukayode, Augustus (Devotion : Journal of Research and Community Service, 2022)
ECOWAS, since 1991, has adopted various instruments which, at least in part, focus on the promotion of democratic governance within member states. Also, for the second time this year, military officers headed by Captain Ibrahim Traore have seized power in the West African state of Burkina Faso, saying they acted because former military ruler, who ousted his democratically elected predecessor in January, failed to address a growing Islamist insurgency. This paper makes an assessment of ECOWAS performance in this respect. Also it discusses the recent developments in Burkina Faso. It concludes by drawing lessons from both the successes and failures of the ECOWAS experience